Kajian Potensi Implementasi Building Information Modeling (BIM) Terintegrasi pada Proses Penanganan Contract Change Order (CCO) dalam Proyek Konstruksi Gedung - Nurhaliza, Meisya Paramita; Sis, Fauzi Septama; Sabrisavira, Fatika Lista; Akmal, Bariq; Ma’wa, Rahila Sabila (Syntax Corporation, 2025)
A Contract Change Order (CCO) is a formal mechanism that accommodates changes in construction implementation, which commonly occur in projects. Although it provides flexibility and adaptability, the CCO process often requires complex coordination and takes considerable time. Therefore, effective management is essential to minimize negative impacts on stakeholders. Implementing integrated Building Information Modeling (BIM) based on a Common Data Environment (CDE) is a digital innovation that may potentially improve the effectiveness of the CCO process. In Indonesia, the use of BIM is increasingly encouraged through the Regulation of the Minister of Public Works and Housing (PUPR) of the Republic of Indonesia Number 22 of 2018, particularly for non-simple state buildings. This study examines the implementation of integrated BIM-based CCO handling in one of the pilot building projects. The methods include a literature review, contract document analysis, interviews, and project data collection. The study found that the reviewed project had implemented CCO handling using three approaches: conventional methods, integrated BIM, and a combination of both. To assess the implementation, a comparison was made between the planned integrated BIM-based CCO process and actual conditions in the field. The analysis revealed that although the integrated BIM approach had been adopted, its implementation still faces several challenges. The main issues identified include the limited number of CDE user accounts, low human resource capacity, delays in 3D BIM modeling, and unclear legal frameworks governing the use of BIM in contract change processes.